Tipos de abonos foliares caseros en las características agronómicas y rendimiento de *Brassica oleracea* L., repollo variedad fuyutokio, loreto, 2024 - Villa Perez, Sol Lucero (2025)
The research was presented using three varieties of homemade foliar fertilizers in order to evaluate their efficacy in Fuyutokio cabbage. A bottom feeding was carried out with poultry manure (30 t/ha) and a dose of 6 ml/liter of water in the active foliar fertilizers. The DBCA Experimental Design and Tukey's evaluation were implemented. The results showed the efficacy of homemade foliar fertilizers, especially type C, to enhance the growth and productivity of Fuyutokio Variety cabbage. The use of these foliar fertilizers, added to the bottom fertilization, contributed to a notable increase in the size, weight and number of leaves, which resulted in a higher yield in the harvest in T4 (type C foliar fertilizer) with 949 g of weight per head and 18,800 Kg/ha. Future research is advised to establish the exact composition of each foliar fertilizer and optimize the doses of use to increase the yield of the product; Additionally, it is crucial to examine the reason for the variation in root length and its link to crop yield.